Fire Protection Systems, Life-Saving Facilities, and Fire Management in Depok City in 2020: A Case Study - Andanari, Maura Wilona; Erwandi, Dadan (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: Hospital fire can result in greater casualties, injuries to patients or staff, and loss of property and equipment compared to fires in other types of building. This is attributed to the presence of a large number of vulnerable individuals, including those who are ill, disabled, pregnant, children, elderly, immunocompromised, on life support, or incapable of moving independently. This study aims to assess the implementation of the fire protection system, life-saving facilities, and fire management in Hospital X. Methods: This was a quantitative study on active fire protection system facilities, passive protection system facilities, live-saving facilities, and fire management as the subjects. Data were collected through observation, interviews, and document review, as well as a checklist and then analyzed by comparing the actual conditions with applicable standards and regulations. The final result was presented as the percentage compliance level and categorization according to the criteria established by the Research and Development Agency of the Public Works Department. Results: The active fire protection system presented a standard fulfillment rate of 53%, categorizing it as poor. The passive fire protection systems similarly demonstrated a poor fulfillment rate at 42%, while the life-saving facilities achieved a 66.7% fulfillment rate, placing them in the quite good category. Additionally, fire management attained an 81% fulfillment level, which falls under the good category. Conclusion: Hospital X has a good fire prevention approach with a standard fulfillment level of 60%.